Intercropping period between species of green manures and organically-fertilized coffee plantation - Cardoso, Rosileyde Golçalves Siqueira; Pedrosa, Adriene Woods; Rodrigues, Mateus Cupertino; Santos, Ricardo Henrique Silva; Martinez, Hermínia Emília Prieto; Cecon, Paulo Roberto (Coffee Science - ISSN 1984-3909, 2018)
The adequate supply of nitrogen to coffee plantation is one of the main challenges of organic agriculture. The aim of the present study was to evaluate the effect of organic fertilization with two legume species in different intercropping periods on nitrogen nutrition, initial growth and productivity of coffee plantation. The experimental design was in randomized blocks, in 2x4 split-plot factorial design, being that the plot consisted of two intercrops (coffee+jack bean and coffee+hyacinth bean) and the four intercropping periods (30, 60, 90 and 120 days after sowing of the legume), and the subplot by 50% and 100% of fertilization for the coffee plantation. The increase in the intercropping period between legumes and coffee plantation favored a greater increase in height and node number of coffee trees, besides showing higher heights when fertilized with 50% of the recommended dose and intercropped with hyacinth bean. The intercropping with the hyacinth bean resulted in a larger crown diameter of coffee trees in 2010 and a larger diameter accumulated in the two evaluated years. Higher N contents were found in coffee trees fertilized with 100% of the recommended dose. The legumes supplied the nutritional requirements of the coffee harvest fertilized with 50% of the dose. The bean yield of the processed coffee is not affected by the intercropping with the green manures of jack bean or hyacinth bean.